Perancangan Ulang Tata Letak Gudang Bahan Baku di PT. XYZ dengan Metode Class Based Storage - Nia Yuliana; Bekti Nugrahadi; Anita Oktaviana Trisna Devi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study aims to redesign the raw material yarn warehouse layout at PT. XYZ using the Class Based Storage method to improve storage and retrieval efficiency. The main problem identified in the warehouse is random item placement, resulting in relatively long retrieval times of approximately 10–15 minutes per pallet. This research applies a descriptive quantitative approach using a case study method. The data used consists of inbound, outbound, and inventory records of yarn raw materials from November 2024 to April 2025. The analysis was conducted using the FSN (Fast Moving, Slow Moving, and Non-Moving) method through the calculation of consumption rate and average stay, combined with ABC classification to determine storage priority. The results show that 9 types of yarn are classified as Class A, 11 types as Class B, and 11 types as Class C. Based on this classification, a new warehouse layout was designed by placing Class A items near the input-output area, Class B items in the middle area, and Class C items in the back area of the warehouse, thereby improving storage efficiency and reducing retrieval time.